Disentangling agglomeration and network externalities: A conceptual typology*. (29th January 2016) - van Meeteren, Michiel; Neal, Zachary; Derudder, Ben; Meijers, Evert; Burger, Martijn
Abstract: Agglomeration and network externalities are fuzzy concepts. When different meanings are (un)intentionally juxtaposed in analyses of the agglomeration/network externalities‐menagerie, researchers may reach inaccurate conclusions about how they interlock. Both externality types can be analytically combined, but only when one adopts a coherent approach to their conceptualization and operationalization, to which end we provide a combinatorial typology. We illustrate the typology by applying a state‐of‐the‐art bipartite network projection detailing the presence of globalized producer services firms in cities in 2012. This leads to two one‐mode graphs that can be validly interpreted as topological renderings of agglomeration and network externalities.